Laparoscopic pyelolithotomy in treating extra-renal pelvic calculi at Sanglah General Hospital: a case series - Made Kurniawan AS; Kadek Budi Santosa (Intisari Sains Medis, 2019)
Background: This study aims to describe our initial experience in treating extra-renal pelvic calculi using retroperitoneal laparoscopic pyelolithotomy techniques in Urology Division, Department of Surgery, Sanglah hospital, Bali.Case Description: There were seven patients enrolled with extra-renal pelvic calculi in this study whereas two of them accompanied by calyx inferior secondary stones. All the patients underwent retroperitoneal laparoscopic pyelolithotomy with DJ Stent applied. The operating time was improving in each procedure, with average time was 110 minutes, VAS at the first day post-operative was 1-2, a drain was removed on the second day, one of them was extended until the sixth day, most patients was discharged on postoperative day 3. All patients were stented for 3 to 4 weeks; The stents were removed with office cystoscopy. All patients were stone free on follow-up imaging.Conclusion: Retroperitoneal laparoscopic pyelolithotomy is a safe alternative for the management of pelvic renal calculi with minimal post-operative pain and shorter length of stay.